Analysis of drug release models from biodegradable nanomodified chitosan based materials - М. О. Кумеда; Л. Б. Суходуб; Л. Ф. Суходуб (Біофізичний вісник)
Background: The problem of drug delivery to the tissue-damaged area of the human body remains relevant. Hydroxyapatite (HA), as one of the best known calcium phosphate (CaP) compounds, is used as an inorganic component of composite materials for drug loading. The organic components in composite materials are biopolymers such as alginate, agarose, chitosan (CS), collagen, and gelatin. Selected C60 nanoparticles are widely used as antibacterial agents and can strengthen the structure of composites. Microwave (MW) irradiation is an exposure method that shortens the synthesis time by significantly increasing the number of nucleation centers, which results the reducing the size of the crystallites formed, which affects the adsorption capacity of the product.